Algunos aspectos fonético-fonológicos del espanol de Colombia - Markič, Jasmina (Linguistica (Ljubljana), 2017)
Colombia is, after Mexico, the second country with the largest number of Spanish speakers in the Hispanic world. More than 90% of their 48 million inhabitants are native speakers of Spanish. Colombian Spanish is a grouping of the varieties of Spanish spoken in this country with specific pronunciation, intonation and, especially, vocabulary. The article deals with some relevant phonetic and phonological aspects of Colombian Spanish, some of them shared with other Hispano-American regions, for instance the seseo (...), and other phenomena present in two Colombian superdialects as defined by Montes Giraldo (the presence or absence of implosive -s or the loss of intervocalic -d-). The article also deals with the extension of yeísmo, (...), in the area of Bogotá and with some phonetic phenomena of the creole language palenquero. The analysis is based on examples from spoken Colombian Spanish corpus PRESEEA and other sources.
Keywords: dialekti; fonetika; kolumbijska španščina; phonetics; Spanish; španščina